Inner speech as a brain mechanism for preconditioning creativity process - Kuznetsov, Illia; Kozachuk, Nataliia; Kachynska, Tetiana; Zhuravlov , Oleksandr; Zhuravlova, Olena; Rakovets, Oksana (East European Journal of Psycholinguistics, 2023)
The current domain of creativity studies is characterized by a high diversity of psychological and neuroscience techniques and methods researchers use. However, the role of verbal processes, especially inner speech, remains underrepresented in this area. Existing studies point to the heterogeneity of inner speech brain mechanisms involved in creative thinking. While consciously controlled verbalized thoughts are associated with the activity of task-dependent brain networks (TPN), especially lateral-frontoparietal network (L-FPN), non-voluntary, mind-wandering thoughts are supposed to correlate with default-mode networks (DMN) activity. While DMN activity leads to an increased number of creative ideas, L-FPN activity results in fewer ideas but increased idea originality. From this point, rest state and state of getting prepared (preconditioning) to task completion, when both mind-wandering and control thoughts occur, are of specific interest. In our study, 49 volunteers completed divergent thinking tasks with rest state and preconditioning state preceded. We later divided all participants into two groups – with low and high creativity levels based on their performance during divergent tasks. EEG was recorded during rest state and preconditioning state and analyzed based on power spectrum and sLORETA data. Our results show an essential role of preconditioning alpha-2 EEG subband in creative thinking performance. The originality of the task solution correlates with the activity of L-FPN structures, while DMN activity does not differ significantly between the two groups.Disclosure StatementNo potential conflict of interest was reported by the authors.* Corresponding author: Oleksandr Zhuravlov, 0000-0002-7823-0338 zhuravlov.oleksandr@vnu.edu.ua